Levels of Adaptation in Dry-Hot and Dry-Cold Climate Zone and its Implications in Evaluation for Indoor Thermal Environment. (2015) - Ren, Yimei; Yang, Liu; Zheng, Wuxing; Song, Xiaoji; He, Wenfang
Abstract: To understand the characteristic of human adaptive thermal comfort in the districts with dry-hot and dry-cold climate type, approach of field survey of thermal comfort has been carried out in Turfan of China. Statistical regression analysis has been used to find out the correlation between human thermal sensation and the operative temperature in winter and summer, and adaptive coefficient (λ) proposed in adaptive PMV model (aPMV) has been used to analyze the levels of adaptation of people there. The adaptive coefficient (λ) is -0.48 for winter and 0.62 for summer. The λ for summer varies from Evaluation Standard for indoor thermal environment in civil buildings in China. This indicates that a special evaluation index of λ should be given for those districts with dry-hot climate type which is although in the same climate zone.